The Effect of Lavender Aromatherapy on Nausea and Vomiting in Pregnant Women in First Trimester of Pregnancy - Putu Noviana Sagitarini; I Dewa Ayu Agra Darmawati; Ni Komang Tri Agustini; Ni Made Candra Citra Sari (Babali Nursing Research)
Background: One of these discomforts that occurs in the first trimester is nausea and vomiting. It’s occurs continuously without proper treatment can interfere with the mother's activities. One of the managements to reduce emesis gravidarum non-pharmacologically is administering lavender aromatherapy. The purpose of this study was to determine the effect of administering lavender aromatherapy to nausea and vomiting in pregnant women in their first trimester.